PELUANG DAN TANTANGAN DALAM PENGELOLAAN WAKAF - Ahmad Muslich (MUADDIB Jurnal Kependidikan dan Keislaman, 2016)
There is a strong tremendous financial owned by Muslims. He was able to change the living standards of people in a short time. As an example, with their awareness of the tithes paying, we see none of the poor, orphans and Muslims were hungry the whole day of Eid al-Fitr, even sometimes it was excessive and difficult to share. Moreover, if the Muslims are aware of the infaq (waqf) and alms, the welfare, prosperity, security and comforts of life will be realized. Endowment is not a new thing. It is a legacy of the Prophet which is very beneficial in the history of Islam. Waqf is a terrible practice with benefits and rewards flowing endlessly. Therefore, endowments must be managed professionally, transparantly and accountably.